2007
DOI: 10.1577/1548-8446(2007)32[21:elvlme]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Localized vs. Large-scale Management: The Example of Tautog in Virginia

Abstract: Choice of management spatial scale is a critical step of any stock assessment, but deciding on a conservative criterion is difficult because of risks associated with any choice. For example, if one large unit is selected when distinct sub‐stocks exist, then some population components may disappear over time. Alternatively, choosing several small management units when one well‐mixed stock exists may lead to costly and ineffective management. We consider the example of tautog (Tautoga onitis). Mortality estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…The authors concluded that if an area was managed on a large-scale, such as the EU minimum landing size for B. undatum of 45 mm, but the area consisted of several sub-stocks which showed real biological differences in terms of population parameters, potential management problems would arise. Such problems would include the inability to detect local stock depletion, and a potential loss of genetic diversity and yield (Tuckey et al, 2007). This study has shown that there is potential for such micro-management measures in Shetland but further research should be conducted examining spatial variation of growth rates and size at maturity in B. undatum before such plans could be developed.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The authors concluded that if an area was managed on a large-scale, such as the EU minimum landing size for B. undatum of 45 mm, but the area consisted of several sub-stocks which showed real biological differences in terms of population parameters, potential management problems would arise. Such problems would include the inability to detect local stock depletion, and a potential loss of genetic diversity and yield (Tuckey et al, 2007). This study has shown that there is potential for such micro-management measures in Shetland but further research should be conducted examining spatial variation of growth rates and size at maturity in B. undatum before such plans could be developed.…”
Section: Discussionmentioning
confidence: 97%
“…However, such measures would have to be reviewed on a region by region basis to assess their practicality. Tuckey et al (2007) evaluated the advantages and disadvantages of large-scale and small-scale (localised) management schemes. The authors concluded that if an area was managed on a large-scale, such as the EU minimum landing size for B. undatum of 45 mm, but the area consisted of several sub-stocks which showed real biological differences in terms of population parameters, potential management problems would arise.…”
Section: Discussionmentioning
confidence: 99%
“…Graphical depiction of catch-curve data can reveal violations of the assumptions. Tuckey et al (2007) discussed the situation in which mortality changes over time or across ages. Jensen (1984) discussed the problem of heterogeneous mortality rates among subpopulations.…”
mentioning
confidence: 99%
“…For fisheries-independent surveys that are repeated over multiple years, year-classes may be observed at several ages and analysed separately (Pope, 1972;Ricker, 1975;Serns, 1986). This approach to year-class strength estimation is referred to as the cohort method (Tetzlaff et al, 2011) or the longitudinal catchcurve method (Tuckey et al, 2007).…”
Section: Introductionmentioning
confidence: 99%